Selection and Application of Beam Pumping Unit for Heavy Oil Production - Bahuda, Raddad S.; Abdallah, Elhassan M.; Mukhtar, Yasir; Khan, Waqar A. (International Journal of Petroleum Technology, 2023)
Beam pumping units were among the first and are still among the most widely used artificial lift systems. This study investigates the components of beam pumping units and the manufacturing mechanism and design procedure recommended by Recommended Practice and the QRod simulator. The API provides API RP 11L Recommended Practice to obtain the values and operating characteristics for each component in dimensionless form. A trial-and-error method is used during the design procedures to determine the best surface and subsurface equipment for a given well's data. When completing a well, the artificial lift method must be considered to ensure that the well is able to be produced at a satisfactory rate. Besides, the procedures created nine cases to compare the requirements of different production rates and depths for a heavy oil well with 14 APIs. A depth of 5,000 ft with a rate of 300 bbl/day and a depth of 7,000 ft with a rate of 500 bbl/day is the specific production rate and depths at which the well will produce. For 300 BBL/Day the tubing size selected was 2-7/8” OD, for this size the suitable plunger size is 2”, and the suitable stroke length was 74in. In cases 6, 8, and 9, all the simulated rod strings were unable to handle the stress imposed by the combination of high depth and high production rate. As a result, all designed systems will fail during production.